(untitled) (Revista Brasileira de Plantas Medicinais, 2024)
The development of biofilms is responsible for 80% of microbial infections, which are highly resistant to conventional antibiotics. The study aimed to assess the antimicrobial activity of essential oils of Mimosa verrucosa Benth. and Illicium verum Hook.f. against planktonic and sessile cells and evaluate toxicity. Thirty compounds were identified, the main ones being a-pinene (12.6%), b-pinene (16.7%) and (E)-caryophyllene (14.2%) for M. verrucosa, and estragole (4.2%) and anethole (86.8%) for I. verum. The minimum inhibitory concentrations of the EO of I. verum (29.40 µg/ml) and M. verrucosa (24.89 µg/ml) against planktonic cells showed 99% efficacy against all cells tested (sensitive and resistant Staphylococcus aureus and Escherichia coli). In sessile cells, essential oils of I. verum and M. verrucosa showed efficacy against sensitive S. aureus. The minimum bactericidal concentration (MBC) test revealed that I. verum caused cell death in sensitive S. aureus and E. coli. However, M. verrucosa only showed bactericidal activity against planktonic cells. Considering the expanding resistance to antimicrobials, the EOs tested represent an important therapeutic option, especially against S. aureus and E. coli, which can produce biofilms on various surfaces, becoming a serious public health problem.